IMPROVEMENT OF ARABIC LANGUAGE TEACHER COMPETENCY BASED ON MULTIPLE INTELLIGENCE CLASSROOM - Safutri, Janniarni Toha; Febriani, Suci Ramadhanti; Hilmi, Danial (IAIN Batusangkar, Indonesia, 2020)
This research aims to determine the efforts made in improving the competence of Arabic teacher through multiple intelligence-based classroom management at SD Plus Al-Kautsar Malang. It used a qualitative approach with a case study research design. The data collection included observation, interviews, and documentation, while analysis techniques relied on Miles and Hubermen’ steps as follow; data reduction, data display, and conclusion. The results showed that the efforts to increase the competency of Arabic teachers through multiple intelligence-based classroom management at SD Plus Al-Kautsar Malang, including the improvement of pedagogic and professional competences. The effort to increase pedagogic competence was giving the training to educators related to the design of a lesson plan, while the effort to increase professional competence is training in applying multiple intelligence during the learning process, such as Multiple Intelligence System (MIS) and Multiple Intelligence Research (MIR) training.